ANALISIS VARIASI FREKUENSI DAN PEMBEBANAN TERHADAP EFISIENSI MOTOR INDUKSI 3-FASA - Kristiawan, Irfan (J-Eltrik, 2025)
In the modern industrial era, regulation or control is required in operating 3-phase induction motors. Regulation or control of 3-phase induction motors is to assist production activities in the industry, so that production activities can run according to the company's functions or objectives. There are two ways to regulate the rotational speed of a 3-phase induction motor. The first way is by changing the number of poles on the induction motor. Then the second way is by utilizing the Variable Frequency Drive (VFD) function. This method is quite effective and widely used in modern industries because the motor speed can be controlled according to the required needs by adjusting the frequency input to the 3-phase induction motor. This study aims to determine the effect of changes in frequency and also changes in loading on the efficiency of 3-phase induction motors. The results of the study will be used as guidelines or technical recommendations to regulate the ideal frequency of the 3-phase induction motor in the embossing machine of PT. Hisamitsu Pharma Indonesia, so that the machine can operate effectively and efficiently. The methods used in this study are direct experiments and data analysis. Key words: 3 Phase Induction Motor, Variable Frequency Drive, Frequency, Efficiency